Knowledge and practice of community pharmacists regarding the safety of drugs during pregnancy: a cross-sectional study from a developing country - Amer A. Koni; Hamzah Qashoa; Abeer Abo Musa; Maen Masri; Walaa Hazem; Sari Taha; Aiman Daifallah; Samah W. Al-Jabi; Amani S Abushanab; Sa'ed H. Zyoud (BMC, 2024)
Abstract Background Drug use during pregnancy can cause unfavorable fetal and maternal outcomes. Information sharing is essential for pharmacists' role within intricate, modern healthcare systems. Community pharmacists (CPs) have demonstrated unsatisfactory knowledge across various pharmacological domains in most developing countries. This study aimed to explore the knowledge and practices of CPs regarding medications and herb safety during pregnancy. Methods A cross-sectional study was conducted in a developing country using a self-administered questionnaire. A sample of CPs working in the northern governorates of the West Bank was selected by convenience sampling. The questionnaire included questions on sociodemographic characteristics, practices and knowledge. Descriptive and inferential statistics were calculated using the Statistical Package for the Social Sciences (SPSS) to analyze the data. Results A total of 207 questionnaires were completed. Most respondents had only a bachelor's degree (89.9%) but did not participate in continuous professional development (CPD) (71.0%). Almost one-third of the CP workload involved dispensing drugs to pregnant women. The majority of the participants reported that they inquire about pregnancy status (59.9%), refer to scientific sources (82.6%), and contact a prescribing physician (51.2%) in cases of uncertainty. A higher knowledge score was associated with receiving a master's degree and CPD programs. Most CPs identified folic acid, paracetamol and amoxicillin as safe, while tetracycline, isotretinoin, enalapril, pseudoephedrine and ibuprofen were among the drugs mostly reported as unsafe. Castor oil, Senna, St. John's wort and ginseng were the most frequently reported herbs as unsafe. Conclusions Despite the gaps in knowledge about herb pharmacology, CPs demonstrated acceptable knowledge and practice regarding drug safety during pregnancy. CPD is recommended for addressing gaps in knowledge and practice. Future research evaluating knowledge and practice may benefit from developing a specific, accurate, validated instrument.